Acute modulation of synaptic plasticity of pyramidal neurons by activin in adult hippocampus - Hasegawa, Yoshitaka; Mukai, Hideo; Asashima, Makoto; Hojo, Yasushi; Ikeda, Muneki; Komatsuzaki, Yoshimasa; Ooishi, Yuuki; Kawato, Suguru (Frontiers in Neural Circuits, 2014)
Activin A is known as a neuroprotective factor produced upon acute excitotoxic injury of the hippocampus (in pathological states). We attempt to reveal the role of activin as a neuromodulator in the adult male hippocampus under physiological conditions (in healthy states), which remains largely unknown. We showed endogenous/basal expression of activin in the hippocampal neurons. Localization of activin receptors in dendritic spines (= postsynapses) was demonstrated by immunoelectron microscopy. The incubation of hippocampal acute slices with activin A (10 ng/mL, 0.4 nM) for 2 h altered the density and morphology of spines in CA1 pyramidal neurons. The total spine density increased by 1.2-fold upon activin treatments. Activin selectively increased the density of large-head spines, without affecting middle-head and small-head spines. Blocking of Erk/MAPK, PKA or PKC prevented the activin-induced spinogenesis by reducing the density of large-head spines, independent of Smad-induced gene transcription which usually takes more than several hours. Incubation of acute slices with activin for 2 h induced the moderate early long-term potentiation (moderate LTP) upon weak theta burst stimuli. This moderate LTP induction was blocked by follistatin, MAPK inhibitor (PD98059) and inhibitor of NR2B subunit of NMDA receptors (Ro25-6981). It should be noted that the weak theta burst stimuli alone cannot induce moderate LTP. These results suggest that MAPK-induced phosphorylation of NMDA receptors (including NR2B) may play an important role for activin-induced moderate LTP. Taken together, the current results reveal interesting physiological roles of endogenous activin as a synaptic modulator in the adult hippocampus.